Study on Aesthetics, Art and Sport: A Perspective towards “Argument from Intertwining” - Shorkend, Daniel (Selected Topics in Humanities and Social Sciences Vol. 1, 2021)
The significant, Enlightenment philosophers in aesthetics, such as Schopenhauer and Hegel form the bedrock of many of our ideas in aesthetics. After briefly unpacking their ideas in this regard, I argue for the inability of such philosophers to deal with non-mimetic art, such as abstract painting and in the process their views on aesthetics only apply to a limited domain of the visual arts. Insofar as this is the case I then put forward an alternative aesthetics that accommodates advances in the arts, namely a metaphoric conception of art. Another way to perceive the metaphorical play of images and/or words is to recognize the difference that analytical philosophers draw between different senses of the word “is” or as in mimetic resemblance. This conception of aesthetics also appears to argue for the pervasiveness of aesthetic experience, thus also undermining the said philosophers’ hierarchical elevation of the arts from common experience. This invites an alternative aesthetics, where sport may be regarded as a kind art. In this regard, the role of metaphor, in both positive and negative ways devolving from the post-modern “language turn” leads to a holistic conception of experience, whether parcelled off as art or sport and this is argued for as the so-named “argument from intertwining”.